Assessment of energy security in West Africa: A case study of three countries - G. Ofosu-Peasah; E. Ofosu Antwi; W. Blyth; E. Effah-Donyina (Heliyon)
The study draws key energy policy lessons by assessing and comparing the energy security performance of Burkina Faso, Nigeria and Ghana. The Energy Security Index with application to West Africa is created from eight dimensions and 24 indicators using a simple additive method and non-statistical induced weights. Study results show that the main energy security challenges in West Africa are low public investment in energy infrastructure (including renewable energy), high energy prices, low electricity access, high energy system inefficiencies, armed attacks on energy infrastructure and deteriorating energy sector governance. The study recommends prioritising investment in electricity sector infrastructure in West Africa.